About the meaning of independency - Fontana, Josep (Cuadernos de Historia, 2010)
By studying the political, economical and social realities that played an important role at the civil war, given the weakness of the troops sent from Spain, culminated in the rise of New States and the problems faced by these States reorganizing the colonial order, this article analyzed the independency revolution as a process conducted by a minority who, on behalf of the whole population, looked for their own benefit more than the common welfare.